PI3K-dependent GAB1/Erk phosphorylation renders head and neck squamous cell carcinoma sensitive to PI3Kα inhibitors - Xu Zhang; Jiao Xu; Xuan Wang; Lan Xu; Xi Zhang; Yi Wang; Shujuan Jiang; Yixiang Zhang; Jian Ding; Chen Qing; Linghua Meng (Cell Death and Disease)
Abstract The hyperactivation of the PI3K pathway in head and neck squamous cell carcinoma (HNSCC) suggests that targeting PI3K is a potential therapeutic strategy. CYH33 is a novel PI3Kα-selective inhibitor discovered by our group, which is currently undergoing a phase I clinical trial (NCT03544905) for the treatment of advanced solid tumors including HNSCC. However, there is an urgent need to elucidate its mechanism of action and improve its efficacy against HNSCC. In this study, we found that CYH33 displayed promising but variable therapeutic activity against HNSCC. Inhibition of PI3K/Akt pathway by CYH33 was not sufficient for its activity against HNSCC. Tandem-Mass-Tag (TMT) phosphoproteomics were performed to reveal comprehensive regulation of kinome by CYH33. Particularly, attenuation of Erk phosphorylation was associated with the sensitivity of HNSCC cells to CYH33. Mechanistically, inhibition of PI3K by CYH33 blocked the PIP3 production and attenuated the membrane localization and phosphorylation of GAB1, resulting in reduced Erk phosphorylation and ultimately inhibition of cell proliferation in sensitive HNSCC cells. Meanwhile, activation of EGFR induced GAB1 phosphorylation independent of PI3K in HNSCC cells. Concurrent inhibition of EGFR synergistically potentiated the activity of CYH33 against HNSCC. These findings revealed the insight mechanism of CYH33 against HNSCC and provided rational combination regimen for HNSCC treatment.